Analysis of micromovements and peri-implant stresses and strains around ultra-short implants - A three-dimensional finite-element method study - Nida Sumra; Shrikar Desai; Rohit Kulshrestha; Khusbhu Mishra; Raahat Vikram Singh; Prachi Gaonkar (Wolters Kluwer Medknow Publications, 2021)
Background: Success of an implant depends on its placement in the bone and how well the stress and strain are distributed to the surrounding structures when occlusal force is applied to it. The size and shape of the implant plays an important role is the formation and distribution of stress and strains in the periodontium. Von Mises stresses and micromovements need to be evaluated while placing implants in D4 bone quality regions for a higher success rate. Aim: To evaluate the peri-implant Von Mises stresses, strains, and micromovements distribution in D4 bone quality around ultra-short implants of 5 mm length with varying diameters of 4 mm, 5 mm, and 6 mm. Materials and Methods: The finite element method was employed to make models replacing maxillary molars in D4 type bone that was missing. Implants that could be classified as ultrashort (5 mm) were used. These implants were of varying diameters of 4, 5, and 6 mm. In each model, the implant was subjected to a force of 100 N and analyzed. The force was applied in an oblique (45 degrees) and vertical direction (90°) to the long axis of the tooth. The models were made such that they simulated cortical and cancellous anisotropic properties of the bone. The models were then analyzed using the program ANSYS workbench version 12.1. Results: When all the three diameters were compared wide diameter, i.e., 6 mm threads had the least values of peri-implant von Mises stresses, strains, and micro-movements around them. When thread shapes were taken into consideration square micro thread created the most favorable stress parameters around them with minimum values of stress, strains, and micromovements. Conclusion: Ultrashort implants combined with a wide diameter and platform switched can be used in atrophic ridges or when there is a need for extensive surgery to prepare the implant site.